Total iron removal from aqueous solution by using modified clinoptilolite - Salimi A.H.; Shamshiri A.; Jaberi E.; Bonakdari H.; Akhbari A.; Delatolla R.; Hassanvand M.R.; Agharazi M.; Huang Y.F.; Ahmed A.N.; Elshafie A. (Ain Shams University, 2023)
Adsorption; Fourier transform infrared spectroscopy; High resolution transmission electron microscopy; Hydrochloric acid; Iron research; Potable water; Scanning electron microscopy; Zeolites; Adsorption capacities; Adsorption process; Characterization methods; Fourier transform infra red (FTIR) spectroscopy; Isothermal modeling; Modified clinoptilolite; Preparation method; Response surface method; Chemicals removal (water treatment)